2021
DOI: 10.1038/s41598-021-83048-9
|View full text |Cite
|
Sign up to set email alerts
|

Urea-functionalized amorphous calcium phosphate nanofertilizers: optimizing the synthetic strategy towards environmental sustainability and manufacturing costs

Abstract: Nanosized fertilizers are the new frontier of nanotechnology towards a sustainable agriculture. Here, an efficient N-nanofertilizer is obtained by post-synthetic modification (PSM) of nitrate-doped amorphous calcium phosphate (ACP) nanoparticles (NPs) with urea. The unwasteful PSM protocol leads to N-payloads as large as 8.1 w/w%, is well replicated by using inexpensive technical-grade reagents for cost-effective up-scaling and moderately favours urea release slowdown. Using the PSM approach, the N amount is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…A significant field of studies still in the initial phase concerns the methods of synthesis of nanofertilizers. A new chemical approach towards a highly efficient post-synthetic modification (PSM) of nACP was recently proposed [68]. The protocol, not particularly complex and expensive, leads to the production of nACP doped with urea (nano U-ACP).…”
Section: Amorphous Calcium Phosphate Nanoparticlesmentioning
confidence: 99%
“…A significant field of studies still in the initial phase concerns the methods of synthesis of nanofertilizers. A new chemical approach towards a highly efficient post-synthetic modification (PSM) of nACP was recently proposed [68]. The protocol, not particularly complex and expensive, leads to the production of nACP doped with urea (nano U-ACP).…”
Section: Amorphous Calcium Phosphate Nanoparticlesmentioning
confidence: 99%
“…Damage to mitochondria can alter the mitochondrial membrane potential, activating Pink1 in the outer mitochondrial membrane, which initiates autophagy (Nguyen et al, 2016). In mouse models of AD, the decrease of Pink can aggravate synapse loss and cognitive dysfunction (Rodríguez-Navarro et al, 2008), which can be mitigated by promoting mitophagy (Du et al, 2017;Fang et al, 2019). Our data show that hippocampal mitophagy in mice was inhibited from 2 months after ovariectomy through at least 3 months.…”
Section: Discussionmentioning
confidence: 68%
“…It was also proven in field applications to be able to save up to 50% of urea consumption. Carmona et al (2021) reported higher NUE (69%) with an efficient N-nanofertilizer obtained by postsynthetic modification of nitrate-doped amorphous calcium phosphate nanoparticles with urea than the conventional fertilizer (49%). However, as with most new technologies, nanotechnology has potential risks such as, undesirable effects on non-target organisms (plants, soil microbes and humans).…”
Section: New N Sourcesmentioning
confidence: 99%
“…Nanofertilizers: Nanosized fertilizers are the new frontier of nanotechnology (Carmona et al, 2021). Nanofertilizers (1-100 nm), due to their small size are highly reactive and have a large surface area, compared to the traditional fertilizer sources that have small surface area and are less reactive.…”
Section: New N Sourcesmentioning
confidence: 99%